2009
DOI: 10.1021/jp902583x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of N + NO Reaction on Rh(111) Surfaces: A precursor-Mediated Reaction

Abstract: We studied the mechanism of the N + NO reaction on Rh(111) surfaces by means of near edge X-ray absorption fine structure (NEXAFS) spectroscopy. Atomic nitrogen layers on Rh(111) were titrated with NO at various temperatures. Below 350 K, the chemisorbed NO monomer does not react with N, while the NO dimer formed in the second layer acts as an extrinsic precursor to the reaction: N(a) + (NO) 2 (a) f N 2 O(g) + NO(a). Because of a dominant role of the precursor-mediated mechanism, the reaction proceeds slower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 53 publications
3
22
0
Order By: Relevance
“…The ignition temperature of 280 °C for the N ad + NO atop reaction under 10 mTorr CO is much higher than those for the N ad + NO atop reaction on CO-precovered Ir(111) (150 °C) 17,28 and for the N ad + NO hollow reaction on Rh(111) (150−200 °C). 28,32 This is probably due to CO poisoning under 10 mTorr CO for Ir(111) where the surface is dominated by high-coverage CO atop as shown in Figure 3(b). CO molecules are more strongly adsorbed on Ir(111) than NO molecules, 16,31 which is an opposite trend to the case of Rh(111).…”
Section: Nap-xps and Ms Resultsmentioning
confidence: 99%
“…The ignition temperature of 280 °C for the N ad + NO atop reaction under 10 mTorr CO is much higher than those for the N ad + NO atop reaction on CO-precovered Ir(111) (150 °C) 17,28 and for the N ad + NO hollow reaction on Rh(111) (150−200 °C). 28,32 This is probably due to CO poisoning under 10 mTorr CO for Ir(111) where the surface is dominated by high-coverage CO atop as shown in Figure 3(b). CO molecules are more strongly adsorbed on Ir(111) than NO molecules, 16,31 which is an opposite trend to the case of Rh(111).…”
Section: Nap-xps and Ms Resultsmentioning
confidence: 99%
“…Below 350 K, the chemisorbed NO monomers do not react with N­(a), whereas the NO dimers formed in the second layer react with N­(a) to give N 2 O­(g) and NO­(a). Above 350 K, the reaction path changes, with N­(a) reacting with NO­(a) to give N 2 (g) and O­(a) …”
Section: Introductionmentioning
confidence: 99%
“…Particularly, synchrotron-radiation-based electrondetecting core-level spectroscopies are quite useful because they are highly surface sensitive and they can provide information on structure and chemical states of both substrate and adsorbate. We have been using such techniques for in situ monitoring of prototypical catalytic surface reactions such as CO oxidation [9][10][11][12], NO reduction [13][14][15] and H 2 O formation [16][17][18] on metal surfaces under UHV conditions. For example, fast-XPS measurements for CO oxidation on Pd(1 1 1) revealed that phase transitions take place under a reaction condition and each oxygen phase exhibits a largely different reactivity and kinetics [10].…”
Section: Introductionmentioning
confidence: 99%